Addivant expands production capacity for Ultranox antioxidant. Issue 2 (February 2018) - Unknown
Abstract : In the USA, stabilizers specialist Addivant has expanded production capacity for its high-performance antioxidant Ultranox ® 626 by more than 40% at its Morgantown plant in West Virginia. The phosphite-based antioxidant is used in the stabilization of a wide variety of polymers, including polyolefins, elastomers and engineering plastics, the company reports. Financial details of the investment have not been revealed.